Suppression of DLBCL Progression by the E3 Ligase Trim35 Is Mediated by CLOCK Degradation and NK Cell Infiltration. (24th May 2021) - Tan, Xiyan; Cao, Fuyang; Tang, Feiyu; Lu, Can; Yu, Qiaoyan; Feng, Songshan; Yang, Zhanghuan; Chen, Songming; He, Xiang; He, Jiang; Weng, Liang; Sun, Lunquan
Abstract : The majority of diffuse large B-cell lymphoma (DLBCL) patients develop relapsed or refractory disease after standard ruxolitinib, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) chemotherapy, which is partly related to a dysregulated tumor immune microenvironment. However, how the infiltration of immune cells is appropriately regulated is poorly understood. Herein, we show that the E3 ubiquitin ligase Trim35 is expressed at low levels in human DLBCL tissues. We also show that overexpression of Trim35 suppresses DLBCL cell proliferation and correlates with inferior survival in DLBCL patients. Our mechanistic study shows that Trim35 functions as an E3 ligase to mediate the ubiquitination and degradation of CLOCK, a key regulator of circadian rhythmicity. High expression of Trim35 correlates with NK cell infiltration in DLBCL, partly due to the degradation of CLOCK. Consistently, patients with high expression of CLOCK show poor overall survival. Overall, these findings suggest that Trim35 suppresses the progression of DLBCL by modulating the tumor immune microenvironment, indicating that it may be a promising diagnostic and prognostic biomarker in DLBCL.